A cross-sectoral integrated assessment of alternatives for climate mitigation in Madagascar. (25th November 2020) - Nogueira, Larissa P.; Longa, Francesco Dalla; van der Zwaan, Bob
ABSTRACT: Using the integrated assessment model TIAM-ECN, we analyze how Madagascar's nationally determined contribution (NDC) to the Paris Agreement can be implemented in both the energy and non-energy sectors. We explore how the country's national climate goal for 2030 can be reached under two different cost levels for climate change mitigation through land-use change. We find that land use is the main sector in which large greenhouse gas (GHG) emission reductions must be achieved, but there are opportunities to also exploit the country's abundant domestic low-carbon energy resources. We explore the options for such a transformation of Madagascar's energy system, which today largely relies on the use of biomass. If GHG emissions reduction in land use is hard or too costly to implement, e.g. as a result of land property rights or forest logging practices, total final energy use needs to be almost entirely renewable by 2050. The power sector needs to rely on 100% renewables already by 2030. In our scenario runs, biomass, hydropower, solar and wind energy account for the vast majority of electricity generation in Madagascar from 2030 onwards. Electrification is introduced in the residential sector – notably for cooking. Cumulative additional undiscounted investment requirements may be as high as US 8 billion up to 2050. Key policy insights Madagascar could reach its 14% GHG emission reduction target relative to 2030 business-as-usual levels through the land use sector only. However, given the potential higher mitigation costs in land use and its links with the energy system, overlooking mitigation options in the energy sector could be a missed opportunity to exploit abundant domestic low-carbon energy resources. Biomass may well remain the most important energy resource in Madagascar until 2050, mainly driven by residential cooking demand. Solid biomass stoves with efficient combustion should be promoted hand-in-hand with alternative fuels, e.g. electricity and bioethanol. Promoting GHG mitigation in both AFOLU and energy sectors maximizes co-benefits, which enables achieving a higher number of sustainable development goals (SDGs). Providing electricity for household services is an important part of climate change mitigation. Investments in power distribution infrastructure and decentralized electricity generation are needed to achieve electrification of rural households.